The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1039/c5tc01205h
|View full text |Cite
|
Sign up to set email alerts
|

Balancing the H- and J-aggregation in DTS(PTTh2)2/PC70BM to yield a high photovoltaic efficiency

Abstract: The content and ratio of two stacking styles, namely H-aggregation and J-aggregation, of 5,5'-bis{(4-(7-hexylthiophen-2-yl)thiophen-2-yl)- [1,2,5]thiadiazolo [3,4-c]pyridine}-3 ,3'-di-2-ethylhexylsilylene-2,2'-bithiophene, DTS(PTTh 2 ) 2 had a profound influence on performance of solar cells based on DTS(PTTh 2 ) 2 /[6,6]-phenyl-C71-butyric acid methyl ester (PC 70 BM) (7/3, w/w) blend films. It was found that the H/J ratio could be tuned from 0.30 to 1.40 by controlling boiling point of main solvent, content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 41 publications
(90 reference statements)
2
28
0
Order By: Relevance
“…It was proved that a balance between the H and J aggregation is need for device to obtain best performance [43]. SVA was found to improve H-aggregation effectively as described above and offered a chance to enhance PCE.…”
Section: To Enhance Pce By Increasing H/j Ratiomentioning
confidence: 93%
“…It was proved that a balance between the H and J aggregation is need for device to obtain best performance [43]. SVA was found to improve H-aggregation effectively as described above and offered a chance to enhance PCE.…”
Section: To Enhance Pce By Increasing H/j Ratiomentioning
confidence: 93%
“…The thin film absorption spectra of M1 and M2 are presented in Figure S3, Supporting Information. Interestingly, M1 and M2 demonstrate different aggregation behaviors, that is, H‐like and J‐like, in the film state, according to the absorption band shift . For M1 , a blue‐shifted absorption band (≈10 nm) is observed from solution state to film state, indicating the formation of H‐like aggregation.…”
Section: Resultsmentioning
confidence: 96%
“…In dilute chloroform solutions, o-4TBC-2F and m-4TBC-2F exhibited wide absorption in the ranges of 300-800 and 300-700 nm with maximum absorption peaks located at 671 and 595 nm, respectively.The absorption spectra of the o-4TBC-2F and m-4TBC-2F films were similar to their corresponding solution spectra with as light broadening and redshift. After thermal annealing of the o-4TBC-2F film at 100 8 8C for 5min, its absorption spectrum dramatically broadened and red-shifted, which indicated that the molecules probably form J-aggregates in the solid state; [12] while the absorption spectrum of m-4TBC-2F remained nearly unchanged before and after thermal annealing. According to the previously reported literature,t he formation of J-aggregates can help construct efficient charge transport channels.…”
Section: Resultsmentioning
confidence: 99%